Recent Breakthrough in Primality Testing - Šleževičienė, R.; Steuding, J.; Turskienė, S. (Nonlinear Analysis: Modelling and Control, 2004)
This paper briefly surveys the history of primality tests. The recently discovered deterministic polynomial time primality test due to Agrawal, Kayal and Saxena is presented and some improvements are shortly discussed.